Anti-Inflammatory and Analgesic Effect: an Experimental Study of Purple Leaves (Graptophyllum pictum (L.) Griff) Decoction - Sondang Khairani; Rika Sari Dewi; Yeshika Krispansis Maelissa (Faculty of Pharmacy Universitas Pancasila, 2025)
Purple leaves (Graptophyllum pictum (L.) Griff) are known to contain flavonoid compounds as anti-inflammatory and analgesic properties. This study aims to obtain the efficacy of purple leaf decoction as anti-inflammatory and analgesic. The anti-inflammatory study used the Winter method with Sprague Dawley rat test, were divided into 5 groups, negative control was only given aquadest, positive control with a dose of diclofenac sodium 8.0208 mg/200g BW, and 3 groups of decoction with doses of 5.4 mg/200g BW, 10.8 mg/200g BW and 21.6 mg/200g BW. Anti-inflammatory testing was carried out by measuring the decrease in the volume of edema on the soles of the rat's feet. Analgesic testing using the Siegmund method with Deutche Denken Yoken mice. The mice were divided into 5 groups, negative control was only given aquadest, positive control with a dose of diclofenac sodium 1.1586 mg/20g BW, and 3 groups of decoction with doses of 1 mg/20g BW, 2 mg/20g BW and 4 mg/20g BW. The analgesic study was carried out by calculating the decrease in the number of writhing mice. The results of the percentage of anti-inflammatory effectiveness of purple leaf decoction doses (5.4 mg/200g BW, 10.8 mg/200g BW and 21.6 mg/200g BW) were 51.77%, 68.77% and 79.46%, respectively. The results of the percentage of analgesic effectiveness of purple leaf decoction doses (1 mg/20g BW, 2 mg/20g BW and 4 mg/20g BW) were 54.03%, 71.62% and 79.73%, respectively. Based on the test results, it can be concluded that purple leaf decoction has an anti-inflammatory and analgesic effect.